Growth and development of Moringa oleifera seedlings, produced in substrates with sewer sludge and bovine manure - Alonso, J.; Vieira, Iago Thomaz do Rosario; Ferrnandes, Mariana Ferreira Rabelo; Rocha, Leonardo Michel; Ferreira, Guilherme Augusto de Paiva; Junio, Gerardo Ribeiro Zuba; Santos, Leonardo David Tuffi; Sampaio, Regynaldo Arruda (Cuban Journal of Agricultural Science, 2021)
The growth and development of Moringa oleifera seedlings, produced in substrates with sewer sludge and bovine manure, were studied. A randomized block design with four replications was applied. A total of 12 treatments were elaborated, plus the commercial substrate Bioplant as a control. During 22 days, the emergence speed index was determined, and before transplantation, physiological and morphological measurements were made and the Dickson quality index was calculated. The physiological measurements were made on a fully expanded leaf and a portable LI-6400 meter was used. The emergence speed index differed between treatments and showed high correlation with respect to the physical properties of the substrate. The physiological indicators were similar, with values between 5.86-9.73 (μmol m-2 s-1) of liquid photosynthesis; 0.02-0.13 (mol m-2 s-1) of stomatal conductance and 1.04-1.76 (μmol CO2 mmol H2O-1) of transpiratory rate. The morphological variables plant height and stem diameter were higher (P <0.0143 and P <0.0077) in the prepared substrates, although some of them did not differ from the control. The number of leaves/plant was lower (P <0.0001) in the commercial substrate. In this treatment, the root volume (8.25 cm3) and the Dickson index (0.56) reached the highest values. The use of sewer sludge and bovine manure in substrates for seedlings production did not affect the growth and development of M. oleifera. Key words: emergency speed index, seedlings production, substrates, Moringa oleifera